Estimation of Volumetric Fraction of Coal Seams in a Thick Layer Using Anisotropy Parameters - Feasibility Study - Pevzner, Roman; Bona, Andrej; Lebedev, Maxim (EAGE, 2014)
We present a feasibility study of using effective VTI anisotropy parameters for estimation of the coal/coal seam fraction in a stack of coal seams and host rock. These parameters can be relatively easily derived from surface seismic data. We illustrate applicability of the method using two examples from Cooper basin, South Australia.